Tráfico internacional sexual de mulheres: análise da jurisprudência do tribunal regional federal da 5ª região acerca da interpretação e aplicação do art. 149-a, do código penal, à luz do que dispõe o protocolo de palermo sobre a questão do livre consentimento - Bezerra, Gabrielle Cristiane Monte (Universidade Federal Rural do Semi-Árido, 2019)
The present work is proposed there is a jurisprudence of the Federal Regional Court of the 5th Region (TRF5) concerning the International Trafficking of Women for the purpose of sexual exploitation. The object is suitable as the new device has been interpreting and applying as a constant group in art. 149-A of the Brazilian Penal Code (CPB), in light of what the Palermo Protocol advocates on the issue of women's free consent. For him, at first, an overview was presented on the issue of international trafficking and a gender issue, permeating a necessary but often confusing differentiation between international trafficking in women and the international media for prostitution. Then, it was the national and international legal instruments that regulate the international trafficking of women, so that they have a theoretical background on the theme, be more in line with the TRF5 jurisprudence on International Trafficking in Women for sexual exploitation fins. , especially, as this arm makes judiciary has been understanding a matter of free consent provided in art. 149a of the Penal Code, as amended in accordance with the provisions of the Palermo Protocol (2004). Thus, a timeframe was made in the selection of data, beginning in January 2016, date of the amendment of the Penal Code, until 07/15/2019, also marking those accidents on the international trafficking of women who treat women in sexual situation in order to investigate the long-term interpretation of the years. In the end, it was not possible to verify situations in which the TRF5 has been applying the provisions contained in art. 149-A, of the CPB, and the Palermo Protocol, regarding the issue of consent as a decharacterizing factor of International Trafficking in Women for the purpose of sexual exploitation. Despite this, criticisms were made of the possibility of the use of conventionality control by the Court in the judgments analyzed, as well as defending actions against the International Trafficking of Women. Finally, it was argued about the need to implement policies to protect the International Migration of Sex Workers, aimed at defending the rights of those who practice paid voluntary prostitution in other states.
Artigo acadêmico
Keywords: Tráfico Internacional de Mulheres; Prostituição; Migração Internacional; Protocolo de Palermo; Livre consentimento; International Trafficking in Women; Prostitution; International migration; Palermo Protocol; Free consent; CIENCIAS SOCIAIS APLICADAS::DIREITO